Dampak Inovasi Produk dan Digital Marketing Pada Pertumbuhan UMKM: Studi Kasus di Sektor Industri Kreatif - Fatkhan, Regita Amalia; Chasanah, Uswatun (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The purpose of this study is to analyze the relationship between product innovation and the expansion of MSMEs in the creative industries through the use of digital marketing strategies. This qualitative study seeks to understand micro, small, and medium-sized enterprises (MSMEs) in the creative sector, their challenges, the impact of digital technology, and the creative approaches they use. This study's findings highlight the significance of e-commerce, data-based decision-making, cooperation, and customer experience as drivers of growth for micro, small, and medium-sized enterprises (MSMEs) in the creative sector. Further, small and medium-sized enterprises (SMEs) in the creative sector might obtain an edge over their competitors by adopting a business innovation strategy and producing one-of-a-kind, new goods and services. New goods and services may be created by MSMEs via the use of digital technology. This can help organizations stay relevant in the market and respond to shifting customer preferences.